Indoleamine 2,3-Dioxygenase and Tolerance: Where Are We Now? - Mellor, Andrew L.; Lemos, Henrique; Huang, Lei (Frontiers in Immunology, 2017)
Cells expressing IDO suppress innate and adaptive immunity to promote tolerance by catabolizing the amino acid tryptophan (Trp) and other indole compounds. Interferon type I (IFN-I) and type II (IFN-II) produced at sites of inflammation or by activated immune cells are potent IDO inducers because mammalian IDO genes contain IFN response elements. Elevated IDO expression by dendritic cells (DCs) is of particular significance because IDO activity converts mature DCs into tolerogenic APCs that suppress effector T cells (Teff) and promote regulatory T cells (Tregs), thereby promoting tolerance. Local Trp depletion and production of immune suppressive Trp catabolites contribute to tolerogenic processes by activating metabolic pathways responsive to amino acid withdrawal and aryl hydrocarbon (AhR) signaling, respectively. Sustained IDO elevation creates local immune privilege that protects tissues from immune-mediated damage and allows tissues to heal. This response occurs in lymphoid tissues when DNA released by dying tissue cells is sensed to induce specialized DC subsets to acquire tolerogenic phenotypes. The tolerogenic effects of IDO also promote tumourigenesis and help establish immune checkpoints in cancer, as malignant cells are protected from immune surveillance. Similar processes may attenuate host immunity to some pathogens that persist in immunocompetent individuals. However, if inflammation with IDO involvement is not resolved, chronic immune activation at such sites causes progressive tissue damage over time. Another effect of sustained IDO activity is enhanced pain sensitivity, as some Trp catabolites produced by cells expressing IDO are neuroactive. In this review, we summarize links between IDO and chronic inflammatory diseases and discuss prospects for exploiting IDO and Trp catabolism to suppress immunity and promote tolerance for clinical benefit, with particular emphasis on protecting tissues from destructive autoimmunity.